Agro-cities as a way to counteract urban poverty. - Elisei, Pietro; Leopa, Sabina; Lopez, Renata; Di Lorenzo, Agostino; Gerundo, Roberto (My University, 2018)
Monterusciello represents a case of urban poverty induced by a natural disaster: the bradyseism of 1983 which shocked and drastically changed the lives of citizens residing in the historic center of Pozzuoli. The political and technical response to the natural disaster emerged through the realization of a new town providing housing for displaced persons. Monterusciello was designed as a new town alternative to the construction models of the late 70s and early 80s: in here, there are no high-density buildings or a lack of public spaces. This new town had high ambitions in terms of planning the new housing settlement, inspired by a classical forma urbis and a human scale architecture. Despite the intellectual and political effort to find an effective solution to a collective drama, which affected most of Pozzuoli's population, many things did not work. The current public administration is making an ambitious attempt to face and solve the many open issue linked to this serious context of urban poverty. The city of Pozzuoli (Metropolitan area of Napoli) is the only city on South-Europe that succeeded to get, in the first round of the extremely competitive call for proposal, the EU financing named UIA (Urban Innovative Action). The project has the courage to propose ground-breaking solutions for very serious and persisting problems linked to urban poverty in the Monterusciello neighborhood. Innovation is embedded in applying the methodology of the permaculture to regenerate the public land available in between buildings of Monterusciello. Thirty hectares of municipal open areas will be transformed into farmland, developed the innovative techniques of permaculture in order to spearhead an economic process and urban growth as a means to combat poverty. This urban agriculture led regeneration is based on a solid participatory planning process that aims to solve the many existing problems on the ground through learning and training actions (schools and youngster as priority target groups), experimentation of production chains at km zero, use of innovative and ecologic techniques in producing goods, design of cooperativistic a business model for the financial sustainability, relevant investment in advanced design of available public land and space, with a special focus on urban landscape related questions. This paper is presenting the urban regeneration adopted strategy in terms of ongoing and experimental planning practices, built up governance relations and creation of a sustainable (economic, socio-cultural; and environmental) development narrative for present and future development in Monterusciello.
Keywords: Mittelstadt; Stadtteil; Armut; Stadtentwicklung; Entwicklungsmaßnahme; Stadterneuerung; Gemeindefläche; Freiraum; Flächennutzung; Landwirtschaft; Urban Farming